2009
DOI: 10.2134/agronj2009.0112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deficit Irrigation and Fertilization on Cucumber

Abstract: Soil water budgets are essential in determining the proper timing and amount of irrigation. Organic fertilizers can be substituted for commercial fertilizers; however, information is sparse on the interaction of irrigation management and nutrient source on cucumber (Cucumis sativus L.) production. Th is study evaluated nutrient source and irrigation management on growth and yield of cucumber grown in the arid area of Egypt. A fi eld experiment was conducted using cucumber grown in northern Egypt at Shibin El-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 17 publications
12
34
0
Order By: Relevance
“…Vegetative growth was larger during fall that had less radiation and shorter day lengths compared to the spring planting. Reference [29] also reported similar findings earlier. LAI had the greatest increase under trickle irrigation compared with furrow irrigation.…”
Section: Leaf Area Index (Lai) Of Potatosupporting
confidence: 78%
“…Vegetative growth was larger during fall that had less radiation and shorter day lengths compared to the spring planting. Reference [29] also reported similar findings earlier. LAI had the greatest increase under trickle irrigation compared with furrow irrigation.…”
Section: Leaf Area Index (Lai) Of Potatosupporting
confidence: 78%
“…According to Amer et al (2009), organic fertilization favors the improvement of texture and the contents of organic matter and nutrients, contributing to the increase in soil water retention and, consequently, meeting the water requirements of the plant.…”
Section: Resultsmentioning
confidence: 99%
“…These results were in agreement with those reported by [12,13], however Mao et al [7] reported a polynomials relationship between ET and yield. In this study, treatment T 1 -100 had the highest yield and treatments T 3 , 4 , 5 , 6 -80 and T 12 -40 gave fairly good marketable yield with economically saving water, fertilizers and pesticide. The result also indicated that the water productivity (WP) increased with decrease the amount of applied water, the WP were 42.3 and 61.9 kgm -3 for T 1 -100 andT 12 -40, respectively.…”
Section: Resultsmentioning
confidence: 61%
“…Agele et al [5] concluded that seasonal crop ET values were greater during reproduction growth stage in the crop. Amer et al [6] concluded that the cucumber yield significantly decreased in linear relationship with increasing water deficit. However, no significant changed when water applied above 100%ETc.…”
Section: Introductionmentioning
confidence: 99%